Topology Optimization of Additive – Manufactured Autonomous Ground Vehicle Mount - Al-Fahoum, Amjed; Elsaaideh, Hamzah A. (Recent Patents on Engineering, 2025)
IntroductionThe existence of substantial amounts of comparatively unused material inside a certain section indicates a deficiency in resource utilization. The existence of stress concentrations leads to a decrease in both the rigidity and durability of the component.MethodsUsing finite element analysis (FEA), additive manufacturing (AM), and topology optimization (TO) together in this work led to a new patent for making a lightweight part for an unmanned ground vehicle (UGV). Topology optimization is crucial for improving the performance of additive manufacturing and achieving design goals. The process of engineering design frequently leads to mechanical design being characterized by heightened complexity and improved efficiency, owing to its need for exploration and iteration. Employing additive manufacturing and topological optimization methodologies, we developed the optimal prototype. Using ANSYS software makes it possible to change the engineering principle of topology optimization so that it works with additive manufacturing. At the same time, we are doing a full evaluation to see if adding topology optimization is possible, taking into account its pros and cons.ResultsThe results of the study reveal that the proposed intervention has the potential to address other stress-related illnesses. The preliminary design proposal projected a cost of 400 Jordanian dinars (JD).ConclusionHowever, through the process of optimization, we successfully achieved the ultimate design at a reduced cost of 200 JD. The revised design not only provides cost savings but also exhibits greater eco-friendliness.
Keywords: optimization